A novel nuclear xenobiotic receptors (AhR/PXR/CAR)-mediated mechanism of DEHP-induced cerebellar toxicity in quails (Coturnix japonica) via disrupting CYP enzyme system homeostasis. (July 2017) - Du, Zheng-Hai; Xia, Jun; Sun, Xiao-Chen; Li, Xue-Nan; Zhang, Cong; Zhao, Hua-Shan; Zhu, Shi-Yong; Li, Jin-Long
Abstract: Di-(2-ethylhexyl)-phthalate (DEHP) is causing serious health hazard in wildlife animal and human through environment and food chain, including the effect of brain development and impacted neurobehavioral outcomes. However, DEHP exposure caused cerebellar toxicity in bird remains unclear. To evaluate DEHP-exerted potential neurotoxicity in cerebellum, male quails were exposed with 0, 250, 500 and 750 mg/kg BW/day DEHP by gavage treatment for 45 days. Neurobehavioral abnormality and cerebellar histopathological alternation were observed in DEHP-induced quails. DEHP exposure increased the contents of total Cytochrome P450s (CYPs) and Cytochrome b5 (Cyt b5) and the activities of NADPH-cytochrome c reductase (NCR) and aniline-4-hydeoxylase (AH) in quail cerebellum. The expression of nuclear xenobiotic receptors (NXRs) and the transcriptions of CYP enzyme isoforms were also influenced in cerebellum by DEHP exposure. These results suggested that DEHP exposure caused the toxic effects of quail cerebellum. DEHP exposure disrupted the cerebellar CYP enzyme system homeostasis via affecting the transcription of CYP enzyme isoforms. The cerebellar P450arom and CYP3A4 might be biomarkers in evaluating the neurotoxicity of DEHP in bird. Finally, this study provided new evidence that DEHP-induced toxic effect of quail cerebellum was associated with activating the NXRs responses and disrupting the CYP enzyme system homeostasis. Graphical abstract: DEHP exposure induced the cerebellar toxicity. DEHP caused CYPs disruption in quail cerebellum. DEHP regulated the CYPs homeostasis by activation of NXRs responses and modulation of the transcription of the CYPs isoforms. The cerebellar P450arom and CYP3A4 might be biomarkers in evaluating the neurotoxicity of DEHP in bird. Highlights: DEHP induces the cerebellar injury in quail. DEHP triggers the AhR/PXR/CAR pathway responses in cerebellum. DEHP disrupts the cerebellar cytochrome P450 enzyme system homeostasis. Cerebellar P450arom and CYP3A4 might be biomarkers of the DEHP neurotoxicity.